Hiring, Motivating, and Retaining Technical Talent in the Public Sector - Debia, Rafael (Global journal of Business and Integral Security, 2024)
Public entities rely heavily on technology to carry out their missions. Highly skilled employees are needed to support the IT infrastructure, develop applications, and maintain and secure their network and the flow of information. As the cost of hardware decreases, the cost of IT talent increases dramatically. The public sector competes with the private sector for these resources. This study explores the tools available for IT managers in the public sector to attract, retain, and motivate employees to achieve high-performance teams. Utilizing a survey and interviews with IT employees of several California State departments, this study explores the most important reasons for public servants to join the public sector and the factors that motivate or demotivate them to stay at their jobs and perform at their top. The public sector offers very competitive extrinsic motivators such as job security, pay, retirement, and benefits, and public servant IT managers can utilize the intrinsic motivators appealing to their team members such as recognition for their contributions, career growth, participation in the decision process, telework, and mature IT governance. This study recognizes the critical role of the direct supervisor on the level of engagement and motivation of their team. The servant leader style supports the appropriate environment for IT talent to thrive; technical professionals like solving problems and prefer the independence to do it their way. They like clear directions and well-established processes promoting a sense of belonging with good communication and personal relationships and supporting their career development. This study’s survey and interviews identified the impact, often overlooked by upper management, of hiring vendors, implementing off-the-shelf solutions, and not sharing the long term strategy.